THE ROLE OF INTERNATIONAL LAW IN EXPORT IMPORT ARRANGEMENTS AND ITS IMPACT ON THE ECONOMY IN INDONESIA - Jadidah, Fikrotul (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM IBLAM), 2023)
International law plays a crucial role in the lives of the international community. Its role is essential in the current era of globalization to bridge any existing issues. Through international legal provisions, states prevent disputes from arising and settle those that have already occurred. In practice, international trade is often equated with exports and imports. Considering the increasingly complex processes of export and import, it would be challenging to apply the regulations of only one country. That is why international law exists, to provide solutions in minimizing differences in regulations between parties. The processes of unification and harmonization of laws come into play. The research questions in this study are: What is the role of international law in regulating exports and imports in Indonesia, and what is the influence of export-import activities on Indonesia's national economic growth? The research method used is normative juridical with a descriptive-analytical research specification. From the results of this study, the following conclusion is obtained: The legal aspects of international trade agreements for exporting and importing goods in Indonesia involve contractual aspects in accordance with the Civil Code Book III on obligations and principles of international law regulated in the Vienna Convention of 1986 and UNIDROIT on the harmonization of international civil law. Meanwhile, the organization of exporting and importing goods follows the provisions issued by the Indonesian government regarding export-import payment procedures and implementation methods in accordance with foreign exchange laws.